Oxidized maize starch: characterization and its effect on the biodegradable films - Part II. Infrared spectroscopy and solubility - Hung, Dao Phi; Phuc, Mac Van; Hiep, Nguyen Anh; Thanh, Trinh Van; Vuong, Nguyen Thien; Nam, Trương Thị; Xuan, Do Dang (Vietnam Journal of Science and Technology, 2017)
The effects of hypochlorite level, i.e. 0.5; 1 and 2 active chlorine g/100g starch, on the properties of oxidized maize starch were investigated by FT-IR and solubility of oxidized starch and starch film. The obtained results shown that there was no difference of IR spectroscopy graph between native starch and oxidized starch. Although the analytical results indicated that there were carbonyl and carboxyl production, characteristic vibrations of these groups exhibiting on IR spectra was not clear due to either not enough content of carbonyl and carboxyl groups or covering of strong other absorptions. Notwithstanding, IR spectra also shown the change of intensity of characteristic vibrations. Moreover, solubility of starch oxidized by the highest oxidant content level experienced highest degree while solubility of this starch shown the lowest level. It means that carboxyl in this molecule starch, to some extent, esterified with hydroxyl of either other starch molecules or glycerol to produce crosslink. The obtained results also illustrated that there was a little scission chain in oxidation process when modifying maize starch by sodium hypochlorite.